Trees matter: Accounting for silvopastoral systems’ contributions to national GHG inventories - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Visibility and reporting of SPS systems in MRV throughout LAC region were assessed by technical working group of experts from 18 countries. A close-up case-studies from 3 countries is presented